Sintonia de controlador utilizando recozimento simulado para amortecimento das oscilações eletromecânicas - Madruga, Elayne Holanda (2020)
Some disturbances can impair stability and generate electromechanical oscillations in electrical power systems. In this work, a robust controller design is presented, whose main objective is to dampen the electromechanical oscillation modes and ensure system stability. In order to ensure the robustness of the control, using a method for selecting the most significant input-output pairs of the system is proposed, using singular values and Relative Gains Matrix. To act on the selected system, H∞ type controllers are used. Here the designed controller was of low order and its parameters were adjusted using Simulated Annealing. A statistical analysis of the parameters was made; from its validation, the controllers were tuned and it was observed that the system was dampened and met the robustness condition. A comparison was also made of the result with other optimization methods; Simulated Annealing showed a good comparative performance. In addition, atypical situations were simulated in the system to analyze the robustness. There was a good reaction to the variation in the interchange power up to a value of 10%, but there was no control effectiveness when a controller was removed. Thus, it was noticed that the designed controller proved to be efficient for non-high uncertainties.